2021
DOI: 10.1111/cns.13648
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hyperactivity of the dorsal raphe 5‐HTergic neurons ameliorates hippocampal seizure

Abstract: Aims Epilepsy, frequently comorbid with depression, easily develops drug resistance. Here, we investigated how dorsal raphe (DR) and its 5‐HTergic neurons are implicated in epilepsy. Methods In mouse hippocampal kindling model, using immunochemistry, calcium fiber photometry, and optogenetics, we investigated the causal role of DR 5‐HTergic neurons in seizure of temporal lobe epilepsy (TLE). Further, deep brain stimulation (DBS) of the DR with different frequencies was applied to test its effect on hippocampal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The dorsal raphe (DR) is the predominant source of 5-HT innervation of the forebrain and is involved in a variety of functions, including anxiety, depression, and sleep-wake cycles, especially increased respiration and arousal induced by elevated levels of CO 2 , which are often impaired by seizures contributing to S-IRA ( Andalman et al., 2019 ; Kawashima et al., 2016 ). Studies have shown that the activity of 5-HT neurons in DR is closely related to epilepsy, and inhibition of hyperactivity of DR 5-HTergic neurons may present a promising anti-seizure effect ( Cheng et al., 2021 ). In addition, physiological studies reported that electrical and chemical stimulation of both rostral and caudal raphe nuclei, including DR, changed respiratory patterns and serotonergic neurons in raphe nuclei projected throughout the VRC (ventral respiratory column), especially PBC ( Morinaga et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dorsal raphe (DR) is the predominant source of 5-HT innervation of the forebrain and is involved in a variety of functions, including anxiety, depression, and sleep-wake cycles, especially increased respiration and arousal induced by elevated levels of CO 2 , which are often impaired by seizures contributing to S-IRA ( Andalman et al., 2019 ; Kawashima et al., 2016 ). Studies have shown that the activity of 5-HT neurons in DR is closely related to epilepsy, and inhibition of hyperactivity of DR 5-HTergic neurons may present a promising anti-seizure effect ( Cheng et al., 2021 ). In addition, physiological studies reported that electrical and chemical stimulation of both rostral and caudal raphe nuclei, including DR, changed respiratory patterns and serotonergic neurons in raphe nuclei projected throughout the VRC (ventral respiratory column), especially PBC ( Morinaga et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a DBA/1 mouse model and PTZ model, photostimulation of DR 5-HTergic neurons in DBA/1 TPH2-ChR2 mice suppressed tonic seizures in most mice, but had no effect on clonic seizures [76]. However, in another mouse hippocampal kindling model of our research which was considered as a type of clonic seizures of TLE, we found that activities of DR 5-HTergic neurons were markedly increased during hippocampal seizures, and time-aligned inhibition of hyperactivity of DR 5-HTergic neurons with method of either optogenetic inhibition of DR 5-HTergic neurons or 1-Hz DR DBS significantly retarded the acquisition of kindling seizures [24]. These researches indicated that DR 5-HTergic neurons may play different roles in different types of epilepsy and functions of other subregions of the raphe nuclei remain to be investigated.…”
Section: Optogenetic Modulationmentioning
confidence: 50%
“…In an experimental absence epilepsy, the spike and wave discharges (SWDs), which may be associated with the impairment of consciousness, propagated to the DR with a short delay as well as the firing rate of the DR neurons evidently increased throughout the whole paroxysm and returned to baseline levels afterwards [23]. Same situation occurred in mice hippocampal kindling seizures, in which the calcium activities of the DR 5-HTergic neurons were significantly increased [24]. In a word, most seizure activities can quickly spread to the raphe nuclei, but the neural activities of the raphe nuclei are interfered diversely in different types of epilepsy.…”
Section: What Happened To the Raphe Nuclei In Epilepsy? Vulnerability...mentioning
confidence: 99%
“…The generalized seizure duration (GSD) was calculated from the time that mice rearing with bilateral forelimb clonus to the end of after-discharge. Mice that experienced 3 consecutive stage 5 seizures were sacrificed for immunochemistry of c-Fos in GS (1.5h after last GS) according to the protocol of our prior research ( Cheng et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%